Effects of a Single Sub-Anesthetic Dose of Ketamine on Postoperative Emotional Responses and Inflammatory Factors in Colorectal Cancer Patients - Ren, Qin; Hua, Ling; Zhou, Xiaofang; Cheng, Yong; Lu, Mingjun; Zhang, Chuanqing; Guo, Jianrong; Xu, Hua (Frontiers in Pharmacology, 2022)
Objective: To investigate the effect of a single sub-anesthetic dose of ketamine on postoperative anxiety, depression and inflammatory factors in colorectal cancer patients. Methods: A total of 104 patients undergoing selective colorectal surgery were included and randomly assigned into 0.1mg·kg-1 ketamine group (K1 group), 0.2mg·kg-1 ketamine group (K2 group), 0.3mg·kg-1 ketamine group (K3 group) or control group (C group). Corresponding doses of ketamine were given intravenously in the K groups (K1, K2 and K3 groups) 5 min before operation, and the same amount of normal saline was given in the C group. The patients' emotional reactions (anxiety and depression) were assessed by the Hospital Anxiety and Depression Scale (HAD), the quality of postoperative recovery was evaluated by the Quality of Recovery-40 (QoR-40) questionnaire, and the levels of IL-6, IL-8 and TNF-α in peripheral blood were detected by enzyme-linked immunosorbent assay (ELISA) on the day before operation and within 24, 48, 72 h postoperation respectively. Pain was estimated by the visual analog scale (VAS) and sedation was assessed with Ramasay score 30 min after extubation. Results The anxiety score (HAD-A) and depression score (HAD-D) of the K3 group were significantly lower than those of the C group postoperation (P<0.05). The QoR-40 score of the K3 group was significantly higher than that of the C group (P<0.05). The serum levels of IL-6, IL-8 and TNF-α in the K3 group were significantly lower than those in the C group (P<0.05 and P<0.01). There were no significant differences in HAD-A, HAD-D, QoR-40 scores or serum levels of IL-6, IL-8 and TNF-α between the K1 and K2 groups and the C group. There were no significant differences in VAS pain score or Ramsay Sedation score among the four groups 30 min after extubation. There were no significant differences in extubation time, postoperative cough, emergence agitation or delirium among the four groups. No dizziness, nausea, vomiting, diplopia or other adverse reactions were found 30 min after extubation. Conclusion A single sub-anesthetic dose (0.3mg·kg-1) of ketamine can significantly improve the postoperative anxiety and depression of colorectal cancer patients, and reduce the levels of IL-6, IL-8 and TNF-.